Clinico-Physiological Alterations After Epidural Administration Of Dexmedetomidine Alone And In Combination With Bupivacaine In Buffalo Calves - Jaiswal, A.; Pandey, S.S.; Parihar , A.S.; Rajput , N. (Indian Journal of Veterinary Sciences and Biotechnology, 2016)
The present study was conducted to evaluate clinico-physiological alterations after epidural administration of dexmedetomidine alone and in combination with bupivacaine in buffalo calves. The animals of dexmedetomidine-bupivacaine group showed quick onset and longer duration and good depth as compared to animals of dexmedetomidine alone group. The recovery was smooth in both the treatments. There was significant decrease in rectal temperature in both the groups while heart rate and respiration rate was decreased non significantly.
Keywords: Clinico-physiological changes; Epidural Dexmedetomidine; Epidural Bupivacaine